THE EFFECT OF BIG FIVE PERSONALITY ON FEAR OF MISSING OUT - Savitri, Inggrid; Wicaksono, Awang Setiawan; Fastari, Chandrania (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC); Vol 1 No 2 (2021): UMGCINMATIC : 1st Rethinking Education during Covid-19 Era: Challange and InnovationDO - 10.30587/umgeshic.v1i2.3499, 2021)
This study aims to examine the influence of the Big Five Personality on Fear of Missing Out. Fear of missing out is the worry that individuals experience when other people experience impressive experiences in their absence, FOMO is characterized by the desire that the Big-Five Taxonomy does not aim to replace the existing system, but acts as an unifier because it can provide an explanation of the general personality system. In this study, the method used is a quantitative method with a population consisting of 284 students and the number of sample is 71 students of the Faculty of Psychology, University of Muhammadiyah Gresik. In this case the researchers used simple random sampling technique. The data analysis technique used multiple linear regression with a significant level of 5%. The result iss obtained that the value of r count = 0.453 then Ho is rejected and Ha is accepted. The result of the coefficient (r2) of r = 0.453 = 0.205, which indicates that the contribution of the Big-Five personality dimension with a fear of missing out is 20.5%, while the rest is by other variables not examined. Based on the data analysis, it can be concluded that there is a simultaneous influence of Big Five personality on fear of missing out.